The Spread of Islam in Sundanese Tatars - Hidayat, Asep Achmad; Supendi, Usman; Syahroni, Roni; Salam, Muhajir (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This research aims to examine the process of Islamization in Sundanese Tatars through a cultural approach as a complement to the limitations of historical evidence, focusing on the role of myths, proverbs, and proverbs in reflecting the cultural readiness of the community The research uses a qualitative method with a cultural analysis approach to Sundanese mythical texts and proverbs that represent the value system and mentality of the community. The findings show that Sundanese myths and proverbs contain values that describe the psychological and cultural readiness of the community to accept the teachings of Islam. The internality of these values shows that Islamization in Sundanese Tatars occurred through a subtle, integrated, and organically occurring cultural process in people's lives. Islamization in Sundanese Tatars does not only depend on historical figures and events, but also on the acceptance of people's culture as reflected in oral traditions. The cultural approach has proven to be able to fill the historiographical gap and provide a more complete understanding of the process of spreading Islam in this region.